Intézményi elemek értékei a nemzeti vagyonban - Török, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Until the recent past economists identified the assets of a nation as the sum of material assets, humán and social capital. However they found, that the differences of the calculated national assets are not proportional to the welfare of the citizens of the compared countries, therefore they looked for further explanatory variables. The specialists of the World Bank according to the results of their research identified an invisible resource, which is the institutional system of the country. Present study examines ten Hungárián institutional components from the aspect of their value and examines how they are contributing to national assets, hereby how they serve the interest of social welfare.